1995
DOI: 10.1083/jcb.130.3.639
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of MAP 4 function in living cells using green fluorescent protein (GFP) chimeras.

Abstract: Abstract. MAP 4 is a ubiquitous microtubule-associated protein thought to play a role in the polymerization and stability of microtubules in interphase and mitotic cells. We have analyzed the behavior of protein domains of MAP 4 in vivo using chimeras constructed from these polypeptides and the green fluorescent protein (GFP). GFP-MAP 4 localizes to microtubules; this is confirmed by colocalization of GFP-MAP 4 with microtubules that have incorporated microinjected rhodamine-tubulin, and by loss of localized f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
127
1
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(135 citation statements)
references
References 70 publications
6
127
1
1
Order By: Relevance
“…(data not shown) showed that disruption of the cytoskeleton did not mobilize the peripheral punctate spots and tubules and that therefore the cytoskeleton probably does not play a role in anchorage of foci at the plasma membrane. The fluorescent marker proteins GFP-MPD (the microtubule-binding domain of the microtubule-associated Olson et al, 1995) and YFP-talin (Pfaff et al, 1998), labelling microtubules and actin filaments, respectively, were used to show that the inhibitors did indeed disrupt the cytoskeleton under these conditions (data not shown), as previously described (Pouwels et al, 2002b).…”
Section: Resultsmentioning
confidence: 99%
“…(data not shown) showed that disruption of the cytoskeleton did not mobilize the peripheral punctate spots and tubules and that therefore the cytoskeleton probably does not play a role in anchorage of foci at the plasma membrane. The fluorescent marker proteins GFP-MPD (the microtubule-binding domain of the microtubule-associated Olson et al, 1995) and YFP-talin (Pfaff et al, 1998), labelling microtubules and actin filaments, respectively, were used to show that the inhibitors did indeed disrupt the cytoskeleton under these conditions (data not shown), as previously described (Pouwels et al, 2002b).…”
Section: Resultsmentioning
confidence: 99%
“…Expression of GFP on its own results in a diffuse distribution throughout the cytoplasm, in many cases including the nucleus [13][14][15]. Pioneering work by Wang and Hazelrigg [6] has demonstrated that GFP can be used as a fluorescent tag for the N-or C-termini of proteins.…”
Section: Gfp-tagged Proteins and Their Subcellular Localisationmentioning
confidence: 99%
“…This protein is involved in mRNA-localisation during oogenesis. Subsequently tubulin [20], Map4 [15], and tau [21] were tagged successfully. In a recent study a recombinant tobacco mosaic virus, expressing the viral movement protein (MP) fused to GFP, was used to infect plant leaves [22].…”
Section: Cytoskeletonmentioning
confidence: 99%
“…4G). Because the level of gene expression between different cells differed in transient assays, we searched for cells expressing high levels of GFP-MBD, which is known to result in microtubule bundling (Olson et al, 1995;Marc et al, 1998). In these cells peroxisome movement was not affected despite the presence of pronounced microtubule bundles.…”
Section: Covisualization Of Peroxisomes and Cytoskeletal Elements Revmentioning
confidence: 99%